(Re)Configuring Hybrid Meetings: Moving from User-Centered Design to Meeting-Centered Design - Saatçi, Banu; Akyüz, Kaya; Rintel, Sean; Klokmose, Clemens Nylandsted (Computer Supported Cooperative Work (CSCW), 2020)
Despite sophisticated technologies for representational fidelity in hybrid meetings, in which co-located and remote participants collaborate via video or audio, meetings are still often disrupted by practical problems with trying to include remote participants. In this paper, we use micro-analysis of three disruptive moments in a hybrid meeting from a global software company to unpack blended technological and conversational practices of inclusion and exclusion. We argue that designing truly valuable experiences for hybrid meetings requires moving from the traditional, essentialist, and perception-obsessed user-centered design approach to a phenomenological approach to the needs of meetings themselves. We employ the metaphor of ‘configuring the meeting’ to propose that complex ecologies of people, technology, spatial, and institutional organization must be made relevant in the process of design. Key Words: Configuration, Conversation analysis, Hybrid meetings, Micro-analysis, User-centered design